"Second generation" refugees and multilingualism: identity, race and language transmission. Issue 14 (14th November 2017) - Bloch, Alice; Hirsch, Shirin
ABSTRACT: This paper explores the language practices, attitudes to languages and the inter-generational transmission of heritage languages amongst the UK-born adult children of refugee parents. The paper draws on empirical data from a research project based on 45 qualitative interviews with three groups of "second generation" refugees, whose parents came as Tamil refugees from Sri Lanka, Kurdish refugees from Turkey and as refugees from Vietnam. The paper explores the ways in which language is central to political discussions and to national policies on race, cohesion, diversity, "Britishness" and citizenship. These debates and policies ignore and often silence the positive role of heritage languages. This paper highlights the importance of heritage languages as a signifier for a number of wider issues of identity, which intersect with race and refugee backgrounds in complex ways.